A capsule-type gelled polymer electrolyte for rechargeable lithium batteries. Issue 53 (16th May 2016) - Li, Wenjun; Li, Zhaohui; Yang, Chenlu; Xiao, Qizhen; Lei, Gangtie; Ding, Yanhuai
Abstract : A capsule-type gelled polymer electrolyte (CGPE) was prepared by integrating trilayer PVDF/L-PMMA/PVDF fibrous membrane with CL-PMMA. Abstract : A trilayer fibrous membrane was integrated by cross-linked PMMA (CL-PMMA) to form a blended fibrous membrane. Owing to encapsulation of the CL-PMMA component, the resultant gelled polymer electrolyte shows high thermal stability, good electrolyte retention and high ionic conductivity, which is suitable for rechargeable lithium batteries.